There was a mistake in the previous one, so I'm re-uploading it with the mistakes fixed
p n q n = 6 p n − 1 + ( 2 n − 1 ) 2 p n − 2 = 6 q n − 1 + ( 2 n − 1 ) 2 q n − 2 p − 1 = 1 , p 0 = 3 q − 1 = 0 , q 0 = 1
Find n → ∞ lim q n p n .
This is a continuation of this problem
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can show, by induction, that q n = ( n + 1 ) ( 2 n + 1 ) ! ! , and it is not hard to see that p n − π q n < ( 2 n + 1 ) ! ! , so that lim n → ∞ q n p n − π q n = 0 and lim n → ∞ q n p n = π .
@Otto Bretscher Wait...what?? Sir, how did you even come to the general formula for the sequence q_n ?????!! I mean, Induction can only be done AFTER we arrive at the formula.........
Log in to reply
If you analyse the ratio r n = q n − 1 q n , as one naturally does in a situation like this, you are led to conjecture that r n = 2 n + 3 + n 1 = n ( n + 1 ) ( 2 n + 1 ) ; for example, r 8 = 1 9 . 1 2 5 , r 9 = 2 1 + 9 1 , r 1 0 = 2 3 . 1 . From here you can write and prove the closed form q n = ( n + 1 ) ( 2 n + 1 ) ! ! rather easily.
Incredibly elegant, Sir Otto!!
Problem Loading...
Note Loading...
Set Loading...
The answer is indeed π .
Lemma: x q n − 1 + ( 2 n − 1 ) 2 q n − 2 x p n − 1 + ( 2 n − 1 ) 2 p n − 2 = ( 6 + x ( 2 n − 1 ) 2 ) q n − 2 + ( 2 n − 3 ) 2 q n − 3 ( 6 + x ( 2 n − 1 ) 2 ) p n − 2 + ( 2 n − 3 ) 2 p n − 3 Proof:
x q n − 1 + ( 2 n − 1 ) 2 q n − 2 x p n − 1 + ( 2 n − 1 ) 2 p n − 2 = x ( 6 q n − 2 + ( 2 n − 3 ) 2 q n − 3 ) + ( 2 n − 1 ) 2 q n − 2 x ( 6 p n − 2 + ( 2 n − 3 ) 2 p n − 3 ) + ( 2 n − 1 ) 2 p n − 2 = ( 6 x + ( 2 n − 1 ) 2 ) q n − 2 + x ( 2 n − 3 ) 2 q n − 3 ( 6 x + ( 2 n − 1 ) 2 ) p n − 2 + x ( 2 n − 3 ) 2 p n − 3 = = ( 6 + x ( 2 n − 1 ) 2 ) q n − 2 + ( 2 n − 3 ) 2 q n − 3 ( 6 + x ( 2 n − 1 ) 2 ) p n − 2 + ( 2 n − 3 ) 2 p n − 3
q n p n = 6 q n − 1 + ( 2 n − 1 ) 2 q n − 2 6 p n − 1 + ( 2 n − 1 ) 2 p n − 2 = [ 6 + 6 ( 2 n − 1 ) 2 ] q n − 2 + ( 2 n − 3 ) 2 q n − 3 [ 6 + 6 ( 2 n − 1 ) 2 ] p n − 2 + ( 2 n − 3 ) 2 p n − 3 = ⎣ ⎢ ⎢ ⎡ 6 + 6 + 6 ( 2 n − 1 ) 2 ( 2 n − 3 ) 2 ⎦ ⎥ ⎥ ⎤ q n − 3 + ( 2 n − 5 ) 2 q n − 4 ⎣ ⎢ ⎢ ⎡ 6 + 6 + 6 ( 2 n − 1 ) 2 ( 2 n − 3 ) 2 ⎦ ⎥ ⎥ ⎤ p n − 3 + ( 2 n − 5 ) 2 p n − 4 . . . = F n q 0 + 1 2 q − 1 F n p 0 + 1 2 p − 1 = F n 3 F n + 1 = 3 + F n 1
Where I've applied the lemma repeatedly and F n = 6 + 6 + 6 + . . . + 6 + 6 ( 2 n − 1 ) 2 . . . 7 2 5 2 3 2
Hence
n → ∞ lim q n p n = n → ∞ lim 3 + F n 1 = 3 + 6 + 6 + 6 + . . . 7 2 5 2 3 2 1 2 = π ( ∗ )
( ∗ ) is a well known continued fraction for π .
Bonus: By considering the sum n = 1 ∑ ∞ n ( n + 1 ) ( 2 n + 1 ) ( − 1 ) n , proof ( ∗ ) using Euler's Continued Fraction Formula.